A cost-effective system for triggering alarm to distracted drivers/ nurses. (June 2019) - Bej, Debabrata; Rakshit, Subhajit; Mal, Ashis Kumar; Mahapatra, Rajat
Highlights: Distraction alarm for drivers/nurses through systematic and sensor-less approach. Cost-effective system design and its application to avoid distraction. Tracking of distraction through pseudorandom events. Identification of distraction from response recording of drivers/ nurses. Abstract: In this study, a systematic, low-cost, sensor-less solution for generating random alarm to distracted drivers/ nurses is proposed and designed to save them from accidents. A simple Finite State Machine (FSM) based algorithm is proposed for this work which has been implemented using an ATmega 328P – PU microcontroller. For testing the status of the driver/nurse, Linear Feedback Shift Register (LFSR) has been used to generate pseudo-random events at arbitrary intervals. In addition to this, a Register Transfer Level (RTL) diagram has also been investigated, and system output has been verified through Field Programmable Gate Arrays (FPGA) simulation. The prototype system has been deployed in a real-life environment by placing it in dashboard of a driver in a running vehicle or by putting the system on desk of a nurse on duty. The effective alertness of the driver and the nurse is found to be 76% and 87% respectively.